Pulping, engineering, environmental, recycling and sustainability (PEERS) : conference proceedings 2015, 2016, 2017, 2018 and 2019. (TAPPI, 2019)
Pulping, Engineering, Environmental, Recycling and Sustainability (PEERS) Conference Proceedings 2015, 2016, 2017, 2018 and 2019, Held 25-28 October 2015, Atlanta, Georgia, USA; 26-28 September 2016, Jacksonville, Florida, USA; November 5-8, 2017, Norfolk, Virginia; 28-31 October 2018, Portland, Oregon, USA; October 27-30, 2019 in St. Louis, MO.